Brikettillverkning på gårdsnivå - Gideskog, Staffan (2008)
In my work I have chosen to examine the profitability for small scale production of hemp briquettes. My study also includes a review of which briquette technique that is the most common one among small scale producers. The reason that I have chosen this subject is because of the discussions about climate and energy that we face almost every day. I also think the subject is extra interesting in these days when the grain prizes are at a historic high level.